2019
DOI: 10.1128/aem.02006-19
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Metazooplankton Filter Feeding on Escherichia coli under Variable Environmental Conditions

Abstract: The fecal indicator bacterial species Escherichia coli is an important measure of water quality and a leading cause of impaired surface waters. We investigated the impact of the filter-feeding metazooplankton Daphnia magna on the inactivation of E. coli. The E. coli clearance rates of these daphnids were calculated from a series of batch experiments conducted under variable environmental conditions. Batch system experiments of 24 to 48 h in duration were completed to test the impacts of bacterial concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 53 publications
5
9
0
Order By: Relevance
“…In this study we found that Daphnia can function as a short-term and transitional host for E. coli: as hypothesised, Daphnia did reduce abundances of E. coli in the surrounding waters but it was not responsible for the complete removal of E. coli, since many bacterial cells survived gut passages (Figure 5) and E. coli was still detected after 10 days of co-culturing with Daphnia (Figures 5 and 6). In this study we confirm that E. coli localizes mainly in the gut of Daphnia and that at least part of its population survives the gut passage (Burnet, et al 2017;Ismail, et al 2019). However, the association with Daphnia obtusa did not seem to give a long term advantage in the survival of E. coli (Figures 6&7).…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…In this study we found that Daphnia can function as a short-term and transitional host for E. coli: as hypothesised, Daphnia did reduce abundances of E. coli in the surrounding waters but it was not responsible for the complete removal of E. coli, since many bacterial cells survived gut passages (Figure 5) and E. coli was still detected after 10 days of co-culturing with Daphnia (Figures 5 and 6). In this study we confirm that E. coli localizes mainly in the gut of Daphnia and that at least part of its population survives the gut passage (Burnet, et al 2017;Ismail, et al 2019). However, the association with Daphnia obtusa did not seem to give a long term advantage in the survival of E. coli (Figures 6&7).…”
Section: Discussionsupporting
confidence: 74%
“…Many studies have recently suggested to use Daphnia as a biological controlling mechanism for E. coli contaminations in water: through experiments using very large densities of animals and bacteria these studies showed that the abundance of E. coli was reduced due to grazing of Daphnia (Nørgaard and Roslev 2016;Burnet, et al 2017;Ismail, et al 2019). The addition of Daphnia is surely feasible to reduce large abundances of E. coli, but here we showed that E. coli persisted even in the presence of Daphnia in low abundances that were more similar to those found in nature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is generally assumed that the presence of Daphnia sp. reduces E. coli abundance in the water ( 37 , 38 ). Nevertheless, in a study based on 16S rRNA gene amplicon sequencing from a lake, E. coli /Shigella made up a large percentage of the copepod and Daphnia microbiota, but were present only at low abundance on stones, in water, and in sediments ( 39 ).…”
Section: Introductionmentioning
confidence: 99%
“…Filter-feeding zooplankton, such as daphnids, are abundant in natural treatment systems; they are a critical link in aquatic food chains and can significantly improve water quality through grazing (Fayer et al, 2000; This article contains online-only Supporting Information. Ismail et al, 2019;Jürgens et al, 1997;Shiny et al, 2005;Trout et al, 2002). Adverse effects of AgNPs on daphnids at environmentally relevant conditions could impact the efficacy of treatment wetlands.…”
Section: Introductionmentioning
confidence: 99%